2021
DOI: 10.1111/ced.14584
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological effects of Curcuma species: a systematic review

Abstract: Summary Curcuma and its derivatives are associated with anti‐inflammatory and antioxidant activities in the skin. They exhibit beneficial effects in wound healing and prevention of chronic ultraviolet B damage and may prevent facial redness such as rosacea and flushing. This review aims to provide an up‐to‐date and rigorous synthesis of studies that demonstrated the clinical efficacy of curcuminoids in the skin. We evaluated studies published in the MEDLINE–PubMed/PMC (National Library of Medicine) databases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 22 publications
0
27
0
1
Order By: Relevance
“…Curcumin has the effect of promoting blood circulation and anti-inflammatory. 8 It may improve blood circulation in hair follicles and promote hair growth. Studies have shown that piperine can increase the serum concentration, absorption, and bioavailability of curcumin in rats and humans without any side effects.…”
Section: Ta B L Ementioning
confidence: 99%
“…Curcumin has the effect of promoting blood circulation and anti-inflammatory. 8 It may improve blood circulation in hair follicles and promote hair growth. Studies have shown that piperine can increase the serum concentration, absorption, and bioavailability of curcumin in rats and humans without any side effects.…”
Section: Ta B L Ementioning
confidence: 99%
“…Among these, pre-treatment with curcumin has been proposed to improve the healing activity of stem cells on diabetic rat wounds (210,332). Evidence obtained in humans indicate that curcumin's vasal activity on peripheral arterioles might be beneficial in reducing face redness and photodamage (16), and indeed curcumin has been proposed for the treatment of rosacea and acne (333). A liposomal gel preparation containing curcumin and lauric acid has been shown to reduce bacterial growth of P. acnes and to reduce comedone counts and cytokines in a rat ear model of acne (334).…”
Section: Skinmentioning
confidence: 99%
“…The recent literature has shown curcumin as one of the most interesting pleiotropic nutraceuticals capable of interacting with different molecular targets involved in inflammation and oxidative stress. Moreover, curcumin showed positive effects as vasculo-and neuro-protective agent (13)(14)(15), and beneficial properties in skin diseases (16).…”
Section: Introductionmentioning
confidence: 99%
“…All these properties have boosted the interest of researchers in this compound in recent decades. Thus, several preclinical studies and clinical trials have been conducted [ 12 ] with the aim of elucidating whether or not curcumin was effective for many different diseases, such as skin [ 13 ], cancer, or neurological pathologies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%